STRATEGI INVESTASI DAN PENINGKATAN PENJUALAN MELALUI SAHAM DAN DESAIN KEMASAN PRODUK MENARIK - Nurlia, Nurlia; Alvaleri, Divka Pradya; Akbar, Pandu Muhammad; Indrayani, Indrayani; Rohman, Dwi Taufik (Gapenas Publisher, 2025)
Rintik Village has great economic potential in the Micro, Small, and Medium Enterprises (MSMEs) sector, but faces obstacles in financial management and product marketing. Low financial literacy means that people have not utilized the capital market as an alternative to managing savings, while MSME products are less attractive due to their simple packaging design. To overcome this problem, a community service program was carried out through socialization and investment training in the capital market and the creation of more attractive MSME product packaging designs. This activity lasted for three weeks using the counseling method, interactive discussions, and the design and delivery of packaging designs to MSME actors. The results of the activity showed an increase in public understanding of stock investment, where participants began to understand the basic concepts of investment, opportunities, and associated risks. In addition, corn cake MSME actors received a new packaging design that was more attractive and in accordance with market needs, thus potentially increasing product competitiveness. In conclusion, this program has succeeded in increasing public financial literacy and helping MSMEs develop their products, although further assistance is needed so that the results achieved can be implemented optimally.